2015
DOI: 10.1590/s1679-45082015ao3472
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of dental fluorosis made by undergraduate dental students

Abstract: Objective To check knowledge of undergraduate dental students to make diagnosis of dental fluorosis with varying degrees of severity and choose its appropriate treatment.Methods Data were collected using a semi-structured questionnaire addressing knowledge of undergraduates based on ten images of mouths presenting enamel changes.Results Only three images were correctly diagnosed by most undergraduates; the major difficulty was in establishing dental fluorosis severity degree.Conclusion Despite much information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
11
1
1
Order By: Relevance
“…The results obtained in the diagnosis of fluorosis in the group of students were different from the results presented in the study done by Rigo et al 16 , in the year 2015, in the same institution. Their research, composed of ten images of different degrees of severity of dental DISCUSSION fluorosis, concluded that only three images were correctly diagnosed by the students, showing that an expressive number of students do not know how to diagnose it in clinical practice 16 . Thus, demonstrating that students are now acquiring more information for clinical decisionmaking.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…The results obtained in the diagnosis of fluorosis in the group of students were different from the results presented in the study done by Rigo et al 16 , in the year 2015, in the same institution. Their research, composed of ten images of different degrees of severity of dental DISCUSSION fluorosis, concluded that only three images were correctly diagnosed by the students, showing that an expressive number of students do not know how to diagnose it in clinical practice 16 . Thus, demonstrating that students are now acquiring more information for clinical decisionmaking.…”
Section: Resultscontrasting
confidence: 93%
“…This fact may represent a need for greater knowledge in the diagnosis of structural defects that affect dental enamel. There is a great concern in educating capable professionals to recognize the alterations and to indicate the appropriate treatment 16 . Regarding the perception of lesions, the patient may not judge the defect as an aesthetic problem and mild fluorosis does not seem to be a concern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in reaching a definitive diagnosis are usually encountered because these defects may have similar clinical presentation. Quantitative defects—commonly termed enamel hypoplasia—result from inadequate or insufficient formation of enamel matrix, generating a decrease in the amount of enamel formed 2 . Local factors such as trauma may lead to hypoplastic enamel, alongside systemic factors such as nutritional deficiency, neonatal illnesses, delayed birth, congenital syphilis and stress 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Solo cuando se conozcan los factores causales de los defectos de esmalte, será posible la prevención. 45 Pocos son los estudios que miden el nivel de conocimiento de los defectos de esmalte, [46][47][48][49] pareciera que se le da mayor importancia en este ámbito a los relacionados con caries dental. 50,51 Sin embargo, los DDE afectan no solo la integridad de la estructura dentaria, sino también acarrean problemas de sensibilidad, estética, función y además problemas de autoestima.…”
unclassified